Examination of Longitudinal Seismic Vulnerability of Shield Tunnels Utilizing Incremental Dynamic Analysis - Dong, Zhengfang; Kuo, Chenyang; Yin, Junhong; Wen, Sen; Liu, Ganzhi; Gou, Yekai (Frontiers in Earth Science, 2021)
In order to study the longitudinal seismic capacity of shield tunnels, this work applies the structural seismic vulnerability analysis, based on incremental dynamic analysis (IDA), to a shield tunnel and explores the ground motion intensity measure suitable for the shield tunnel in different site types. The failure probability of the structure at each earthquake intensity is calculated by combining the probabilistic seismic demand model with the limits on the engineering demand parameters to establish the seismic vulnerability curve of the structure. The results indicate that the peak ground velocity (PGV) is the ground motion intensity measure suitable for the longitudinal seismic performance of the shield tunnel. The site type has the most profound influence on the extent of the longitudinal damage to the shield tunnel, and site type IV is the most dangerous under an earthquake. Further, the tunnel has stronger seismic resistance in the elastoplastic stage. The low-grade bolts between the rings damage more severely than the high-grade bolts. A tunnel with either a great depth of burial or a large cross section is more dangerous than the one with either a small depth of burial or a small cross section. The risk of the axial tension-compression failure of the shield tunnel is higher than that of the horizontal transverse shear failure.